Leaf emergences in Microlepis oleaefolia (DC.) Triana (Melastomataceae) and their probable function: An anatomical and ultrastructural study - Milanez, Camilla R. D. [UNESP]; Machado, Silvia R. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
Microlepis oleaefolia (D.C.) Triana, an endemic species of Melastomataceae from the Brazilian cerrado, presents very complex leaf structures called as "hairs with root-like base" embedded in the mesophyll. This paper describes the ontogenesis, histochemical and structural aspects of these leaf structures as a framework for further functional studies. Samples of leaves in different developmental stages were processed according to common light and electron microscopy techniques. Fresh material was subjected to histochemical tests to examine the chemical composition of cell walls. The apoplastic transport between leaf emergences and the vascular system was verified by staining with 1% aqueous safranin. The structures are emergences of mixed protoderm and ground meristem origin. They are persistent, predominantly short-stalked and dendritic. Their arms have thick non-lignified cellulosic walls with a loose and heterogeneous aspect; on the inner face, the wall, which appears labyrinthine, presents small irregularly shaped projections directed towards the protoplast. The base of the emergences is composed of sclereids embedded in the mesophyll that reach the vascular system. Assays with aqueous safranin solution revealed it penetrates the cell walls of the arms and showed a connection between the emergence and xylem. Anatomical, chemical and ultrastructural features of leaf emergences of M. oleaefolia indicate that these structures are able to transport substances via apoplast and can absorb or exude solutions. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: emergences; melastomataceae; Microlepis oleaefolia; ontogeny; structure